2020
DOI: 10.1007/s00204-020-02953-6
|View full text |Cite|
|
Sign up to set email alerts
|

Cytochrome P450 expression, induction and activity in human induced pluripotent stem cell-derived intestinal organoids and comparison with primary human intestinal epithelial cells and Caco-2 cells

Abstract: Human intestinal organoids (HIOs) are a promising in vitro model consisting of different intestinal cell types with a 3D microarchitecture resembling native tissue. In the current study, we aimed to assess the expression of the most common intestinal CYP enzymes in a human induced pluripotent stem cell (hiPSC)-derived HIO model, and the suitability of that model to study chemical-induced changes in CYP expression and activity. We compared this model with the commonly used human colonic adenocarcinoma cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 50 publications
(87 reference statements)
1
18
0
Order By: Relevance
“…These results indicate that organoids on day 15 already express intestine-specific markers but are fairly immature, whereas by day 30 the in vitro maturation culminates. This is in accordance with findings from Spence et al (2011) and Janssen et al (2020) . After 50 days in culture, we observed a general decrease in the expression of most markers, although still in detectable levels, showing that organoids’ functionality in culture gradually deteriorates from day 30 days.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results indicate that organoids on day 15 already express intestine-specific markers but are fairly immature, whereas by day 30 the in vitro maturation culminates. This is in accordance with findings from Spence et al (2011) and Janssen et al (2020) . After 50 days in culture, we observed a general decrease in the expression of most markers, although still in detectable levels, showing that organoids’ functionality in culture gradually deteriorates from day 30 days.…”
Section: Resultssupporting
confidence: 93%
“…These stainings were performed at 30 days post Matrigel embedment of hindgut organoids or their transfer to suspension culture. This time-point was selected according to Spence et al (2011) and Janssen et al (2020) , who demonstrated that intestinal organoids embedded in Matrigel can reach sufficient maturation after approximately 28 days. Organoids from both culture conditions showed similar expression patterns of the mentioned markers.…”
Section: Resultsmentioning
confidence: 99%
“…iPSC derived HIOs consist of enterocytes, goblet cells, mesenchymal and enteroendocrine cells [25][26][27][28] . Furthermore, iPSC derived HIOs have shown improved cytochrome P450 and transporter expression in comparison with Caco-2 cells 29,30 . More recently, iPSCs have been used to create 2D intestinal epithelial cell (IEC) layers that emulate the full cellular complexity of the 3D HIOs, but have an easily accessible apical and basolateral side in comparison with their 3D HIO variants which are closed spheres.…”
mentioning
confidence: 99%
“…Successful recovery of cryopreserved organoids ( 44 , 145 ) can provide a banked resource for future use. Furthermore, organoids are useful for standard biological analyses such as live cell imaging using inverted phase-contrast and confocal microscopies ( 101 ), gene expression analysis ( 14 ), genetic modification ( 146 ), and enzyme activity assay ( 14 ).…”
Section: Evolution Of Organoid Culture Systemsmentioning
confidence: 99%
“…Although many studies have been conducted on organoids in humans and mice ( 5 , 14 , 15 ), studies focusing on organoids in farm and companion animal species have been gaining attention in various fields including veterinary and translational medicine as well as biomedical research. This is because companion animals that develop spontaneous chronic disorders similar to those of humans have been suggested to serve as better models of human patients than traditional murine models where the disorders are usually genetically or chemically induced ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%